Associations of intrinsic capacity, fall risk and frailty in old inpatients - Shen, Shanshan; Xie, Yanhong; Zeng, Xingkun; Chen, Lingyan; Guan, Huilan; Yang, Yinghong; Wu, Xiushao; Chen, Xujiao (Frontiers in Public Health, 2023)
Introduction This study explored the associations of intrinsic capacity (IC), fall risk, and frailty in geriatric inpatients. Methods A total of 703 hospitalized patients aged 75 years or older were recruited for this retrospective observational study from Zhejiang Hospital using a comprehensive geriatric assessment. The IC composite score was constructed from the scores of the Chinese version of the Mini-Mental State Examination, Short Physical Performance Battery, Short Form Mini Nutritional Assessment, 15-item Geriatric Depression Scale, and self-reported hearing and vision impairment. Adverse outcomes were recorded as the fall risk and frailty using the Morse Fall Scale and the Clinical Frailty Scale. Spearman’s correlation coefficient analyses and multivariate logistic regression models were used to explore the associations between IC, high fall risk, and frailty. Results Declined IC composite scores were associated with increased risks of falls [odds ratio (OR) = 0.64, 95% confidence interval (CI): 0.57–0.72] and frailty (OR = 0.45, 95%CI: 0.37–0.54) among older hospitalized patients after adjusting for the related potential confounders. In addition, decreased cognitive, vitality, locomotion, and psychological scores were associated with increased adverse health conditions, with ORs ranging from 0.26 to 0.70. Vision impairment was observed to increase the risk of frailty (OR = 0.42, 95%CI: 0.23–0.76) after adjusting for the related potential confounders. Discussion This study indicated that declined IC was associated with fall risk and frailty in older inpatients. Further prospective studies are needed to explore the longitudinal associations between baseline IC and subsequent risk of falls and frailty.